YOUNG LEARNERS’ PROBLEMS IN ENGLISH WRITING - Adila Jefiza (UIN Sumatera Utara Medan, 2016)
Writing still becomes a big problem for students, especially for young learner students. They thought that writing is the most difficult skill compared the other language skills. This study was conducted by using qualitative method in order to give more description about students’ writing problems. Twelve elementary school students in the fifth grade were chosen purposely as participants. The data were collected by observing students and teacher activities in the classroom. Then, some students were interviewed to get further explanation about their problems. After that, students’ writing were analyzed . The result of this study confirmed that students has problem in spelling words, grammar and choosing vocabularies. It is expected this research will help teacher in developing available strategies for teaching writing and can be a basic information for further research.Key words: writing, English writing, young learners